In-house age-specific reference ranges for free light chains measured on the SPAPlus® analyser. (March 2020) - Campbell, Lauren; Simpson, Dawn; Shields, Adrian; Ferry, Berne; Ramasamy, Karthik; Sadler, Ross
Background: The measurement of monoclonal free light chains is being increasingly utilized since the introduction of serum-based assays. It is important for laboratories to determine their own reference ranges in order to reflect the local population. The aim of this study was to determine if age-adjusted reference ranges for serum free light chains would have implications for demand management of further laboratory investigations including immunofixation. Methods: After certain exclusions, 4293 samples from individuals seen in primary care across Oxfordshire between 2014 and 2016 were identified for analysis of patient characteristics, serum free light chain results and estimated glomerular filtration rate. Results: We found age to be an independent variable when considering serum free light chain concentrations, ratio and estimated glomerular filtration rate. The reference ranges derived from our data differ markedly from the original Binding Site ranges. When the age-specific ranges are retrospectively applied to our population, there is a 38% decrease in follow-up testing with no loss of specificity. Conclusion: We feel confident implementing new age-specific serum free light chain reference ranges in our laboratory. We have developed a simple algorithm for evaluating serum free light chains based on age and estimated glomerular filtration rate. We encourage laboratories to establish their own local reference ranges using large cohorts and their chosen serum free light chain assay platform.